DEVELOPMENT OF ACHIEVEMENT MOTIVATION TRAINING MODEL BASED ON BOSEKA TRADITIONAL GAMES IN ELEMENTARY SCHOOL STUDENTS - Widati Amalin Ulfah; Dedy Putranto (Universitas Negeri Medan, 2019)
The low motivation of students and there was no physical education teacher innovation to package a more interesting learning process. This study aimed to develop a model of achievement motivation training based on traditional boseka games for elementary school students. This research method used research and development methods from Borg and Gall 1983 which have been modified by researchers namely: (1) Requirement analysis of 25 students for observation; (2) Manufacture of initial products; (3) Overview of experts 3 persons; (4) Product revision; (5) Small group trials 10 students; (6) Product revision; (7) Large group trials 14 students; and (8) The final product. Based on the results of the study obtained data from expert evaluations with an average percentage of 85.70% (feasible), from the results of small-scale trials obtained an average percentage of 79.3% (feasible) and for large-scale trial results obtained by an average of an average of 89.3% (feasible). Thus it was concluded that the development of achievement motivation training model based on the traditional game boseka was appropriate to be used for students in high school elementary